Structural phase transition to disorder low-temperature phase in [Fe(ptz)(6)](BF4)(2) spin-crossover compounds - Kusz, Joachim; Zubko, Maciej; Neder, Reinhard; Guetlich, Phillipp (Acta Crystallographica Section B: Structural Science, 2012)
In the spin-crossover compound [Fe(ptz)(6)](BF4)(2) (where ptz=1-n-propyltetrazole) six different phases are observed. When a single crystal is slowly cooled from high temperatures to those below 125 K, the reflections broaden into diffuse maxima and split into two maxima along the c* direction [Kusz, Gutlich & Spiering (2004). Top. Curr. Chem. 234, 129-153]. As both maxima are broad along the c* direction, the short-range order exists only along the c direction and in the ab plane the structure remains long-range ordered. In this disordered phase additional satellite reflections appear. Upon heating above 135 K, the diffuse maxima return to their previous shape and this process is completely reversible. Rapidly cooled samples, on the other hand, do not show such splitting and the symmetry remains R (3) over bar, despite a jump in lattice parameters. We use a special technique to analyse the disorder model of the slowly cooled samples, which consists of layered domains shifted in the hexagonal ab plane. The low-spin disordered phase was solved in a novel approach to accommodate the very unusual twinning and refined in the non-standard space group C (1) over bar. In contrast to the ordered low-spin phase, the Fe ion is in a non-centrosymmetric coordination polyhedron and two of the six propyl groups change their conformation.